The multiple transformations of peacekeeping and its actors: A comparative analysis of Burundi and Somalia - Kumalo, Liezelle (My University, 2014)
Peacekeeping operations often involve more than one actor. With regard to an intrastate war, a peaceful resolution of a conflict often involves external actors. For the purpose of this study the actors have been divided into three groups: local, regional and global, and four variables were identified to determine what influences a decision of each actor to deploy a peacekeeping mission. The study therefore seeks to understand the relationship and interplay between the various actors within the peace process. Recent studies have focused on different international organisations peacekeeping efforts, yet the transformations of one actor to another are not well understood. In this study two civil wars are explored and four hypotheses are identified to explain the transformations.